Akibat-Akibat Pengalihan Pengumpulan dan Peyaluran Zakat dari Penguasa kepada Individu - Sumrowi, Adi R Pawi (State Islamic University of Datokarama Palu, 2022)
This research aims to analyze the effect of shifting the role of collecting and channeling Zakat from the authority to the individual by a full scale and to study the methods of said shifting based on Quran and Sunnah. The researcher conducted an inductive approach in tracing his findings from the Qur’an, Sunnah, and sources that directly relate to this research, in addition to literature reviews. This research contains three chapters. The first chapter discusses Zakat’s derivation in Arabic and the Syariah term. The second chapter is about the main weakness in Zakat’s application. While in chapter three, the researcher concluded this research by showing the effect of Zakat’s shifting in collecting and channeling. The researcher had come to several conclusions, the most prominent is collecting and channeling Zakat are authority’s role, not individual. The researcher recommended studying Zakat’s purpose because Zakat’s application purposes in Syariah will be clear by studying it.